A comparison of the diagnostic utility of the sFlt-1/PlGF ratio versus PlGF alone for the detection of preeclampsia/HELLP syndrome. (2nd July 2016) - Stepan, H.; Hund, M.; Gencay, M.; Denk, B.; Dinkel, C.; Kaminski, W.E.; Wieloch, P.; Semus, B.; Meloth, T.; Dröge, L.-A.; Verlohren, S.
Abstract: Objective : The Elecsys ® immunoassay sFlt-1/PlGF ratio and the Triage ® PlGF assay were compared (in a prospective, multicenter, case-control study) for diagnosis of preeclampsia/hemolysis, elevated liver enzymes, low platelets (HELLP) syndrome. Methods : Women in European perinatal care centers with singleton pregnancies were enrolled: 178 cases had confirmed preeclampsia and 391 controls had normal outcome. Patients in the preeclampsia/HELLP syndrome group were matched pairwise by gestational week to healthy controls (1:2). Maternal blood samples were analyzed using (a) fully automated Elecsys PlGF and Elecsys sFlt-1 immunoassays with two cutoffs (early-onset [<34 weeks] ≤33, ≥85; late-onset [≥34 weeks] ≤33, ≥110), and (b) Triage PlGF immunoassay (single cutoff). Diagnostic performance and utility were assessed. Results : Respectively, 83 and 95 women had early-onset or late-onset preeclampsia/HELLP syndrome. The overall diagnostic performance of the Elecsys immunoassay sFlt-1/PlGF ratio (area under the curve [AUC] 0.941) was higher than for Triage PlGF (AUC 0.917). The Elecsys immunoassay sFlt-1/PlGF ratio sensitivity and specificity was: 94.0% (95% confidence interval [CI] 86.5–98.0) and 99.4% (95% CI: 96.8–99.9) for early-onset preeclampsia; and 89.5% (95% CI: 81.5–94.8) and 95.4% (95% CI: 91.7–97.8) for late-onset preeclampsia. The Triage assay sensitivity and specificity was: 96.4% (95% CI: 89.8–99.3) and 88.5% (95% CI: 82.8–92.8) (early-onset); and 90.5% (95% CI: 83–96) and 64.5% (95% CI: 57.8–70.9) (late onset). Conclusions : The fully automated Elecsys immunoassay sFlt-1/PlGF ratio provides improved diagnostic utility over the Triage PlGF assay with improved specificity for the clinical management of pregnant women with suspected preeclampsia/HELLP syndrome.